PENGARUH PENEKANAN ANGGARAN PADA KINERJA APARATUR DENGAN MODEL PERENCANAAN ANGGARAN SEBAGAI VARIABEL PEMEDIASI - Witnyaningsih, Dwi (Pascasarjana Universitas Sultan Ageng Tirtayas, 2017)
This study aims to examine between budget emphasis, differentiation strategies, budget planning models and performance. Data collected by using questionnaire gave to the officials in SKPD in Banten Province, such as the Head of Department, secretary of the SKPD, and head of subsection/head of sub-field, and the section head. The measurement of data using a Likert scale of 7. Tools of analysis using Partial Least Square (PLS) 2.0. The results show that the role of budgeting planning model as an intervening variable in the relationship between budget emphasis, differentiation strategy and performance. Keyword : budget emphasis, differentiation strategy, and performance.